1990
DOI: 10.1007/bf02274843
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR1 and DRw6 association in DR4-negative rheumatoid arthritis patients

Abstract: This study of 110 seropositive rheumatoid arthritis (RA) patients confirms the significant association of susceptibility to RA with HLA-DR4 specificity (P less than 0.001). The DR1 frequency is elevated in the entire seropositive patient group, reaching marginal significance (P less than 0.025). The DR4-negative patients, however, have a much higher prevalence of DR1 (P less than 0.001). Surprisingly, the DRw6 specificity is significantly increased in the remaining DR4- and DR1-negative patients (P less than 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…1), as well as HLA–DR3 (where *0301 is the major subtype associated) in Kuwait (11, 21). Furthermore, protective effects were reported for DRB1*07 (3, 13, 22–25), *1201 (26), *1301 (24, 26–28), and *1501 (29, 30). Multivariate logistic regression analysis was performed using the SPSSX package (SPSS, Chicago, IL).…”
Section: Methodsmentioning
confidence: 99%
“…1), as well as HLA–DR3 (where *0301 is the major subtype associated) in Kuwait (11, 21). Furthermore, protective effects were reported for DRB1*07 (3, 13, 22–25), *1201 (26), *1301 (24, 26–28), and *1501 (29, 30). Multivariate logistic regression analysis was performed using the SPSSX package (SPSS, Chicago, IL).…”
Section: Methodsmentioning
confidence: 99%
“…He was treated with oral gold salts, prednison (5 mg/day) and non-steroidal anti-inflammatory drugs, but received no immunosuppressive therapy. The result of human leucocyte antigen (HLA) typing by serological methods and by sequencing HLA-DRB genes amplified by polymerase chain reaction was: A2, B5, B60, DR4w4, DRw13(6)-Dw19, DRw52c, DQwl, DQw3 [24,25]. PTW underwent arthroscopic synovectomy-a technique giving rise to a cell suspension immediately after the operation, without further manipulation.…”
Section: Methodsmentioning
confidence: 99%
“…Protective alleles operate conspicuously in insulin-dependent diabetes melitus (IDDM), where certain HLA-DQ alleles associated with HLA-DR2 show this type of negative association with disease (Thomson et al 1988;Baisch et al_ 1990;Zeliszewski et al 1992;Kockum et al 1993). In rheumatoid arthritis (RA), negative association has been found for HLA-DR2 (Jarequemada et al 1986;Ollier et al 1986;Stasny et al 1988;Mehra et al 1993), HLA-DR5 (Jarequemada et al_ 1986; Lang et al 1990), and HLA-DR7 haplotypes (Jarequemada et al 1986;Walker et al 1986), although the latter observation has not been confirmed in N. Avrion Mitchison (~) • Monika C. Brunner Deutsches Rheuma-Forschungszentrum, Nordufer 20, D-13353 Berlin, Germany other studies (Rigby et al 1991). HLA-DR7 (DRBI*07) is protective in early onset pauciarticular juvenile chronic arthritis (Paul et al 1993).…”
Section: Introductionmentioning
confidence: 99%